How do Environmental Quality and Technology Affect Public Debt in Indonesia? A Time Series Analysis - Azikin, Ilham Syah; Utina, Dian Anggriani; Maddatuang, Bahtiar; Baharuddin, Nurfaisah; Ridzuan, Abdul Rahim; Rahman, Nur Hayati Abd (International Journal of Energy Economics and Policy, 2024)
In recent years, Indonesia has grappled with a notable surge in public debt, underscoring the urgency of prudent fiscal management. This study employs the Autoregressive Distributed Lag (ARDL) method to investigate the long-term connections between key variables, including gross domestic product, gross domestic investment, gross domestic savings, carbon emissions, and technology, using data from 1990 to 2020. Our findings reveal a significant and negative association between savings and environmental degradation with Indonesia’s public debt. These insights bear substantial policy implications, emphasizing the importance of integrating environmental considerations into economic planning and suggesting that the banking sector could enhance fiscal stability by incentivizing increased savings rates. This study provides valuable guidance for policymakers and economists seeking to foster Indonesia’s economic resilience in the face of mounting public debt.